ANALISIS EFISIENSI USAHATANI TOMAT (Lycopersicon esculentum Mill) DI DESA SEGOROGUNUNG KECAMATAN NGARGOYOSO KABUPATEN KARANGANYAR - Mahananto Mahananto; Kusriani Prasetyowati; Aris Wardoyo (JURNAL ILMIAH AGRINECA, 2018)
In Indonesia, one of the tomato production areas is located in Karanganyar. This is because Karanganyar has a highland whose environmental conditions are suitable for the cultivation of tomato plants. One of the largest production centers of tomato plants in Karanganyar City is located in Ngargoyoso district. located in Segorogunung village. The general problem of tomato farmers is how to combine the factors of production optimally to produce the high prodution so that get maximum profit. This study aims to determine : (1) the amount of production costs, revenue, and income, (2) factors affecting tomato production levels, (3) efficiency level of production factor use in tomato farming in Segorogunung village. The method use in this research is descriptive analysis survey. The result of the research have shown that : (1) the amount of production cost is as big as Rp. 5.257.044/UT/MT, total acceptance of Rp. 12.052.833/UT/MT and revenue of Rp. 6.795.789/UT/MT. (2) factors of production that have significant effect on tomato production are labor production factor, land area, seedlings, KCl fertilizer, NPK fertilizer, ZA fertilizer and pesticide, while the production factor of cage manure and chicken manure has an unstable effect. (3) factors of labor production, seeds, manure, KCl fertilizer, NPK fertilizer are still not efficient, while the factors of production area of land, chicken manure, ZA fertilizer, and pesticides are inefficient.